KORUPSI, KOLUSI, NEPOTISME DAN SUAP (KKNS) DALAM PANDANGAN HUKUM ISLAM - Huzaemah T. Yanggo (IAIN Ambon, 2017)
Corruption, Collusion, Nepotism and Bribery (CCNB) in the current last few years are many occurred in our country. Therefore it is necessary to study the characteristics of corruption, collusion, nepotism and bribery particularly according to the Qur’an perspective. They reflected behavior, either taken in personal or collective related to the government world adversed to the people, nation and the state. CCNB in the Qur'an perspective is one part of action to “consume someone else's property without right,” so that it was forbidden (haram) to conduct corruption, collusion, nepotism and bribery. But special to nepotism is forbidden if the people who the positions given was not professionals, had not capability and morality in accordance with the Qur'an and Hadith teachings. Corruption, Collusion, Nepotism and Bribery was prohibited, because contrary to the Qur’an, Hadith and maqashid al-Syari'ah (goal of Sharia) teachings, and contrary to the humanity and justice sense, and adverse others people, society and the state. Keywords: corruption, collusion, nepotism, bribery, Islamic law